2020
DOI: 10.7717/peerj.8262
|View full text |Cite
|
Sign up to set email alerts
|

Rapid digitization to reclaim thematic maps of white-tailed deer density from 1982 and 2003 in the conterminous US

Abstract: Background Despite availability of valuable ecological data in published thematic maps, manual methods to transfer published maps to a more accessible digital format are time-intensive. Application of object-based image analysis makes digitization faster. Methods Using object-based image analysis followed by random forests classification, we rapidly digitized choropleth maps of white-tailed deer (Odocoileus virginianus) densities in the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 16 publications
(22 reference statements)
4
17
2
Order By: Relevance
“…Overall in the southeastern United States, white‐tailed deer population size increased from a minimum of <215,000 during 1915–1930 (Blackard 1971) to 304,000 by 1940 (Newsom 1969), 476,000 by 1950, 2.41 million by the 1960s (Newsom 1969), 2.94 million to 4.12 million by approximately 1970 (Blackard 1971), 6.17 million by 1982, to 10.79 million or about 12 million by approximately 2003 (for 2005 in Adams and Ross 2015 and Southeast Deer Study Group 2002–2006; Tables 1 and 2). Please note that similar results during 1982 and 2003 for the continental United States, including the southeastern states, are presented in Hanberry and Hanberry (2020). Mean deer densities in the southeastern United States increased from 0.22 deer/km 2 during 1940 (Newsom 1969), 0.35 deer/km 2 during 1950 (1950 map), 2.2 to 3.1 deer/km 2 during approximately 1970 (Blackard 1971, 1970 map), 4.6 deer/km 2 during 1982 (1982 map), to 8 deer/km 2 or 9 deer/km 2 during about 2003 (for 2005 in Adams and Ross 2015 and Southeast Deer Study Group 2002–2006).…”
Section: Resultssupporting
confidence: 61%
See 3 more Smart Citations
“…Overall in the southeastern United States, white‐tailed deer population size increased from a minimum of <215,000 during 1915–1930 (Blackard 1971) to 304,000 by 1940 (Newsom 1969), 476,000 by 1950, 2.41 million by the 1960s (Newsom 1969), 2.94 million to 4.12 million by approximately 1970 (Blackard 1971), 6.17 million by 1982, to 10.79 million or about 12 million by approximately 2003 (for 2005 in Adams and Ross 2015 and Southeast Deer Study Group 2002–2006; Tables 1 and 2). Please note that similar results during 1982 and 2003 for the continental United States, including the southeastern states, are presented in Hanberry and Hanberry (2020). Mean deer densities in the southeastern United States increased from 0.22 deer/km 2 during 1940 (Newsom 1969), 0.35 deer/km 2 during 1950 (1950 map), 2.2 to 3.1 deer/km 2 during approximately 1970 (Blackard 1971, 1970 map), 4.6 deer/km 2 during 1982 (1982 map), to 8 deer/km 2 or 9 deer/km 2 during about 2003 (for 2005 in Adams and Ross 2015 and Southeast Deer Study Group 2002–2006).…”
Section: Resultssupporting
confidence: 61%
“…Population estimates from distribution maps overall were similar to estimates from other sources, and may be no worse, considering the uncertainty involved. Nationwide estimates also matched well with other sources of estimates (Hanberry and Hanberry 2020). For the Southeast Deer Study Group (2002–2006), reported mean deer densities typically ranged considerably from year to year or did not change at all.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Because bison herbivory reduces C 4 grass dominance it offsets the effects of fire on plant species richness (Hartnett et al, 1996; Collins et al, 1998; Knapp et al, 1999; Fuhlendorf and Engle, 2004; Spasojevic et al, 2010). However, with the decline of historical bison populations (Lott, 2002) and the increase of woody encroachment and fragmentation in these grasslands (Briske, 2017), browsers such as white‐tailed deer ( Odocoileus virginianus ; hereafter deer) have increased in density (Hanberry and Hanberry, 2020). The shift in herbivore pressure from the grazing pressure of bison to the browsing pressure of deer could be playing a large role in restructuring the plant community composition in present‐day North American tallgrass prairie.…”
Section: Introductionmentioning
confidence: 99%